Boosting performance: Through supply chain capabilities and technology adoption - Lee, Khai Loon (UMP Publisher, 2022)
In today’s dynamic business environment, competition is no longer between firms, but between supply chains. The supply chain dependency leads the business to focus on boosting the supply chain performance. Considering the importance of business focus given to the third industrial master plan by the Malaysian government, the current supply chain environment accentuated the need for supply chain technology adoption to boost supply chain performance. To explain the concerns, this book identified the issues and problems related to the supply chain operational performance. Besides, this book provides extensive information on supply chain operational performance, technology, and supply chain capabilities, namely relational capability, information technology capability, and organizational culture capability. In addition, this book further discusses the impact of supply chain capabilities on supply chain operational performance and investigates whether supply chain technology adoption mediates supply chain capabilities and performance in Malaysia’s Textile and Apparel industry.